Pengaruh Strategi Bisnis Perusahaan Dan Financial Reporting Irregularities Terhadap Fee Audit - Pajriati, Merry; Handayani, Deby; Agusman, Agusman (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2022)
The purpose of this research is to determine and analyze the influence of company business strategy and financial reporting irregularities on the size of external audit fees in manufacturing companies listed on the IDX in 2022. This research uses a descriptive and quantitative analysis model with multiple regression analysis methods. The variables used in this research are the company's business strategy and financial reporting irregularities as independent variables and the external audit fee variable as the dependent variable. The technique used to determine the sample in this research is a purposive sampling method using 16 samples of manufacturing companies listed on the BEI in 2022. Based on the research results, it shows that the significance value for the business strategy variable (X1) in external audit fees is 0.002 < 0 .05. With these results it can be stated that the company's business strategy has a significant influence on external audit fees. The significance value for the financial reporting irregularities variable (X2) is 0.001 < 0.05. With these results it can be stated that financial reporting irregularities have a significant effect on external audit fees. In the F test, the calculated F value = 14.637 with sig = 0.000 < 0.05. This means that the variables, company business strategy and financial reporting irregularities simultaneously influence external audit fees in manufacturing companies listed on the IDX in 2022. Based on the results of research that has been conducted, the variables of company business strategy and financial reporting irregularities have an adjusted R square value of 0.169 which is explains that the variables of company business strategy and financial reporting irregularities together have a significant effect on external audit fees in manufacturing companies listed on the IDX in 2022 amounting to 16.9% and the remainder is influenced by other factors not included in this research.